2009
DOI: 10.1002/pro.282
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte‐induced conformational changes in the Hsp90 molecular chaperone

Abstract: Osmolytes are small molecules that play a central role in cellular homeostasis and the stress response by maintaining protein thermodynamic stability at controlled levels. The underlying physical chemistry that describes how different osmolytes impact folding free energy is well understood, however little is known about their influence on other crucial aspects of protein behavior, such as native-state conformational changes. Here we investigate this issue with the Hsp90 molecular chaperone, a large dimeric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 39 publications
(59 reference statements)
2
44
0
Order By: Relevance
“…Previous work demonstrated that osmolytes affect the conformational state of Hsp90, but have little influence on its ATPase activity (33). Work from Auton and Bolen (34) has suggested that the energetic influence of osmolytes originates primarily from the exposure of the peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that osmolytes affect the conformational state of Hsp90, but have little influence on its ATPase activity (33). Work from Auton and Bolen (34) has suggested that the energetic influence of osmolytes originates primarily from the exposure of the peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Hsp90 is a highly flexible molecule and adopts distinct conformations during its functional cycle, which is regulated in turn by a variety of cofactors 3,[6][7][8][9] , as is also the case for Hsp70 (ref. 3).…”
mentioning
confidence: 89%
“…Mechanisms other than competition of choline and glycine betaine for the same ligand-binding site come to mind: (i) binding of glycine betaine to an allosteric effector site in GbsR influencing the occupancy of the choline-binding site and (ii) opposing effects of choline and glycine betaine on dimer formation of GbsR. Alternatively, glycine betaine might not bind directly to GbsR at all and might instead exert its regulatory effects indirectly through its "chemical chaperone" function (16,17) that can influence protein folding and conformation (7,8,56). Osmoprotectants other than glycine betaine can tune down choline-mediated GbsR-dependent induction of gbsAB expression.…”
Section: Subtilis (48) and Chox (K D 2 M) From Agrobacterium Tumefmentioning
confidence: 99%